2018
DOI: 10.1021/acs.inorgchem.8b00301
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric Properties of Variants of Cu4Mn2Te4 with Spinel-Related Structure

Abstract: Thermoelectric properties of CuMnTe, which is antiferromagnetic with a Néel temperature T = 50 K and crystallizes in a spinel-related structure, have been investigated comprehensively here. The phase transition occurring at temperatures 463 and 723 K is studied by high-temperature X-ray diffraction (XRD) and differential scanning calorimetry (DSC), and its effect on thermoelectric properties is examined. Hypothetically CuMnTe is semiconducting according to the formula (Cu)(Mn)(Te), while experimentally it show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…[29][30][31][32] Incidentally, some tellurides with spinel-related structures have also been found lately with relatively high thermoelectric performance. 33,34 Although some attractive themoelectric properties have been reported for thiospinel compounds in the family of the general composition CuM2S4, such as CuCo2S4, CuTi2S4, CuCr2S4 and their derivatives (where Co, Ti, Cr are partially substituted for each other), [29][30][31][32]35 not much information is available on the thermoelectric properties of Sn-based thiospinel compounds and their derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32] Incidentally, some tellurides with spinel-related structures have also been found lately with relatively high thermoelectric performance. 33,34 Although some attractive themoelectric properties have been reported for thiospinel compounds in the family of the general composition CuM2S4, such as CuCo2S4, CuTi2S4, CuCr2S4 and their derivatives (where Co, Ti, Cr are partially substituted for each other), [29][30][31][32]35 not much information is available on the thermoelectric properties of Sn-based thiospinel compounds and their derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the initial dataset (i.e., for the testing set), we have employed the above TL model to predict the ZT of eight randomly selected systems from literatures. [53][54][55][56][57][58][59] There are 19 p-and 27 n-type entries by considering the temperature dependence, which are summarized in Part 5 of the Supporting Information. As shown in Figure 4 (red points), our results exhibit good agreements with those measured experimentally, which is demonstrated by high PCCs of 95% and 94% for the p-and n-type systems, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Interpreting (4 – y )Cu + yTM + 2Mn + 4Te → (4 – y )/4Cu 4 Mn 8/(2–y) Te 4 + y TMTe (TM = Co, Ni), the formation of the TMTe precipitates is imperative in terms of optimizing the carrier concentration, as it results in a slightly higher content of Mn in the matrix and a consequent decrease of hole concentration toward the optimal region. …”
Section: Resultsmentioning
confidence: 99%
“…For example, Guo et al found that its low κ is strongly related with its high Gruneisen parameter, low Debye temperature, and low speed of sound. 40 Chen et al, for the first time, studied the synergistic effect of Te deficiency and Cldoping in ternary Cu 4 Mn 2 Te 4 and achieved a 100% enhancement in zT (=0.4) at 700 K. 41 Li et al systematically assessed Cu 4 Mn 2 Te 4 with different carrier concentrations and demonstrated that zT = 1.0 is achievable when the carrier concentration is tuned to ∼3−4 × 10 20 cm −3 utilizing the canonical single parabolic model. 42 They also revealed the underlying physics of Cu 4 Mn 2 Te 4 , such as deformation potential and density of effective mass.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation